Recommendation System for Determining Micro, Small and Medium Enterprise Business Locations - Eko Budi Setiawan; Angga Setiyadi; Wildan Agung Prakoso (Universitas Multimedia Nusantara, 2020)
From entreprenurship perspective, determining the right business location is, of course, will become a significant factor for the business's growth in the future. Therefore, a system to facilitate prospective and strategic business locations, for achieving the right selling targets is sure needed. Android mobile based system with GPS technology features can make it easier to determine business location. In our application, we try to tackle this problem by using Simple Additive Weighting (SAW). We took several criteria for strategic business location decision making in our SAW implementation, which comprehend of rental rates, accessibility, location crowd, target market, security, and the number of competitors. Then, by evaluating the finished application, we concluded that the development of an application for Micro, Small and Medium Enterprises (MSMEs) recommendations is to facilitate prospective entrepreneurs to determine a strategic business location to build an entrepreneur.